Post-mortem Frequency of Unintentional Injury-related Deaths at a Tertiary Care Hospital - Ummara Munir, Syed Perwez Alam, Hafiza Naima Anwar, Farooq Ahmed Abro, Aisha Rasheed, Mobin Inam Pal, Marvi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Post-mortem investigations are important in determining the cause of death, particularly in cases of unintentional injuries. Despite the global public health concern posed by unintentional injuries, there is a scarcity of data on such deaths in the Hyderabad region of Sindh province, Pakistan. Objective: To investigate the frequency and causes of unintentional injury-related deaths through forensic autopsies conducted in a tertiary care hospital. Study design: Observational and prospective study Place and duration of study: Medico-legal Section, Liaquat University Hospital, Hyderabad from 1st January 2021 to 31st December 2022. Methodology: One hundred and seventy seven road traffic accidents and drowning emerging as prevalent causes of unintentional injury-related deaths were enrolled. Prior consent was diligently sought from the deceased individual’s close relatives to ensure ethical considerations were met throughout the study. Results: Road traffic accidents accounted for over 50% of the total autopsies each year, followed by drowning at more than 25%. Together, road traffic accidents and drowning contributed to approximately 80% of unintentional injury-related deaths annually. Conclusion: The high prevalence of road traffic accidents and drowning underscores the need for comprehensive policies and strategies by government, public health planners, and law enforcement agencies. Addressing factors such as inadequate access to secure environments and insufficient awareness regarding drowning prevention can help reduce drowning-related deaths. Similarly, strict enforcement of traffic rules and infrastructure improvements can mitigate the incidence of road traffic accidents and related fatalities. Keywords: Unintentional injuries, Road traffic accidents, Drowning.